QITCHEN Enterprise / Balqis Syahmina Abdul Aziz ... [et al.] - Abdul Aziz, Balqis Syahmina; Mohamad, Mazzatul Husna; Mohd Nizam, Nur Azmina Syakirah; Megat I’dil Mahfuz, Putri Laila Zahrah; Suhaimi, Shahira (2021)
Qitchen Enterprise is a start-up company establishment located in Senawang, Negeri Sembilan. The company is equally owned and managed by five partners. Qitchen Enterprise expected to catch the interest of a regular loyal customer base with its variety of Korean cakes products that sells under a bakery named Crafty Cakes. Furthermore, Qitchen Enterprise also plans to build a strong market in Senawang town due to the less competition on that area and it is near to the housing area and located near well-known restaurants so that our premise is easy to find by customers. Our bakery, Crafty Cakes offers a variety of high-quality Korean cake such as Red Velvet Cake, Chocolate Cake, Vanilla Cake and Pandan Gula Melaka Cake with a beautiful design and at a reasonable price during business operations to our target market at all times. All cakes are baked and prepared if there is an order from the customer to ensure the cakes are fresh. Besides, we also sell ready-made cakes with unique designs so that the customer can grab the cake at the bakery at the very last minutes for special events. We hope that Crafty Cakes will be a well-known bakery throughout Malaysia and will be able to provide a greater product to our customers from time to time. We believe that the demand of our cakes will increase every year as we build a strong position in the town and in the country by continuing to offer high-quality cakes at a reasonable price to customers